The role of ownership structure as a moderating variable in the relationship between fundamental factor and firm value in companies in the property development and operations subsector - Mimi Jamilah; Rachmawaty Rachmawaty; Sri Retnaning Sampuraningsih (PT Wim Solusi Prima, 2026)
This study aims to examine the influence of fundamental financial factors on firm value and to investigate the moderating role of managerial ownership in the relationship between liquidity, profitability, solvency, and firm value. The research employs a quantitative approach using panel data regression analysis. Secondary data were collected from the annual reports of companies operating in the property development and operation sub-sector listed during the 2018–2024 period. The sample was selected using a purposive sampling technique, resulting in nine eligible companies with a total of 63 firm-year observations. Firm value was analyzed as the dependent variable, while liquidity, profitability, and solvency served as the independent variables. Managerial ownership was incorporated as a moderating variable to evaluate its ability to strengthen or weaken the relationship between financial fundamentals and firm value. The empirical findings indicate that, collectively, liquidity, profitability, and solvency have a statistically significant effect on firm value. However, the partial test reveals that each of these financial indicators does not individually exert a significant influence on firm value. Furthermore, the moderation analysis demonstrates that managerial ownership significantly moderates the relationship between liquidity, profitability, and solvency and firm value. These findings suggest that managerial ownership plays an important governance role by aligning management and shareholder interests, thereby enhancing the effectiveness of financial performance in influencing firm value. The study contributes to the literature on corporate finance and corporate governance by highlighting the importance of ownership structure in strengthening the relationship between financial fundamentals and firm value.